Compressive failure of quasi-static indented CFRP/aluminium honeycomb sandwich panels. (April 2019) - Japins, Guntis; Kalnins, Kaspars; Ozolins, Olgerts; Skukis, Eduards
Abstract: The present study examines sandwich panels, which are made of carbon fiber facesheets with aluminium honeycomb core and focuses on how varying factors (skin thickness, layup, core density and diameter of hemispherical indenter) are affecting collapse of artificially damaged panels in edgewise compression. Damage in the middle of sandwich specimens was introduced using quasi-static indentation. Hemispherical indenters of two diameters, namely, 20 mm and 150 mm, were applied. The residual strength was estimated through the edgewise compression test of damaged specimens. The study demonstrated that increase of the honeycomb density led to decrease in the safety margin in structure. Thicker skins may also lead to a catastrophic propagation of indent.